Implementasi Project-Based Learning melalui Proyek Miniatur Ekosistem untuk Meningkatkan Kreativitas Siswa Kelas V di SD Negeri Winajaya III Karawang - Sartika Ratnayu (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study examines the implementation of the Project-Based Learning (PjBL) model through a miniature ecosystem project to enhance the creativity of fifth-grade students at SD Negeri Winajaya III. The research employed a quasi-experimental design with a pre-test and post-test group. The results revealed a significant improvement in students' creativity after implementing the PjBL model. Students demonstrated increased abilities in designing, developing, and evaluating projects. Additionally, PjBL facilitated collaborative and independent learning. These findings highlight the relevance of PjBL to the Merdeka Curriculum, which emphasizes project-based learning to foster 21st-century skills.